Back Cover: Cadmium–Aluminum Layered Double Hydroxide Microspheres for Photocatalytic CO2 Reduction (ChemSusChem 8/2016). Issue 8 (20th April 2016) - Saliba, Daniel; Ezzeddine, Alaa; Sougrat, Rachid; Khashab, Niveen M.; Hmadeh, Mohamad; Al‐Ghoul, Mazen
Abstract : The Back Cover picture shows the use of layered double hydroxides based on cadmium and aluminum (CdAl LDH) for the photocatalytic reduction of CO2 . Due to the large mismatch of the ionic radii of cadmium and aluminum, CdAl LDH is thermodynamically unstable. To improve its stability an agar gel mix is used as a framework in which LDH self‐assembles in the presence of cadmium and aluminum salts, giving rise to a hierarchical microporous structure. Under solar illumination, the material converted CO2 efficiently to CO. Palladium‐decorated CdAl LDH shows a significant improvement in the reduction potential at room temperature. More details can be found in the Full Paper by Saliba et al. onpage 800 in Issue 8, 2016 (DOI:10.1002/cssc.201600088 ).